Synthesis of highly substituted heterocycles - Trippier, P; Trippier, Paul Charles (2006)
This thesis is concerned with studies towards the total synthesis of a class of natural products - the oxazolomycins. Attention was focused on the left-hand side triene fragment and right-hand side lactam heterocyclic system. This thesis describes the synthesis of a racemic terminal phenyl analogue of oxazolomycin A and C, possessing the left-hand side triene geometry as required. A novel truncated pyridine analogue is also described. The molecules represent a racemic total synthesis of analogues of phthoxazolin A and inthomycins B and C. The synthesis is based upon a crucial Stille cross-coupling reaction between stannane and diene iodide fragments. The stannane fragment was synthesised using literature precedented methods and the vinyl halide prepared using a highly stereoselective Wittig, Takai homologation or Stork reaction leading to a variety of ratios of mixtures of Z, E and E, E diene halides. These investigations led to the availability of 1:1, 3:1 and 1:3 mixtures of Z, Z, E : Z, E, E left hand side triene fragments possessing the required stereochemistries for oxazolomycin A and C. Utilising existing methodology developed in the Moloney group, investigations were carried out towards construction of β-keto esters possessing terminal hydroxyl functions, suitable for diastereoselective aldol ring closure. Following extensive protecting group manipulation and N-acylation coupling optimisation, a TIPS protected β-keto acid, existing as predominantly the keto tautomer, was successfully coupled to an oxazolidine heterocycle. This N-acylated oxazolidine upon Dieckmann cyclisation would present an advanced intermediate of opposite configuration (Lserine is used here as a cheaper starting material for the construction of the oxazolidine instead of D-serine) to the oxazolomycin right-hand side.